(untitled) (Scientific journal of the Fergana State University, 2025)
The requirements for developing and conducting complexes of gymnastics exercises for preschool children are important processes aimed at the physical development of children, the formation of a healthy lifestyle, and the increase of motor activity. This annotation analyzes the significance of gymnastics exercises for preschool children, their impact on development, as well as the main requirements that should be considered when organizing classes. The article outlines the fundamental principles and approaches that will help effectively organize complexes of gymnastics exercises for preschool children. This process is crucial for the development of children’s physical culture, the establishment of a healthy lifestyle, and the creation of a solid foundation for their future physical activities.